Pengaruh Penggunaan Model Pembelajaran Numbered Head Together (NHT) Terhadap Hasil Belajar Biologi Siswa SMP Negeri 1 Mappedeceng - ridha yulyani wardhi (Jurnal Biogenerasi, 2022)
This study aims to determine the effect of the use of the Numbered Head Together Method on the Biology Learning Outcomes of Class VIII Students of SMP Negeri 1 Mappedeceng on the Human Digestive System. This study used a pretest-posttest control group design. The research sample for Class VIII SMP Negeri 1 Mapdeceng was 25 students. The results showed that the learning outcomes of class VIII students of SMP Negeri 1 Mapdeceng before using the Numbered Head Together learning model were in the low category of 34.57. The learning outcomes of class VIII students of SMP Negeri 1 Mappedeceng after using the Numbered Head Together learning model are in the high category of 78.05. It can be concluded that there is an effect of using the Numbered Head Together learning model on the Biology Learning Outcomes of Class VIII students at SMP Negeri 1 Mappedeceng